Some Studies on PWM Converter Controlled Wind Energy Conversion System (International Journal of Engineering and Computer Science, 2014)
Wind power is a green renewable source of energy that can compete effectively with fossil fuel as a generator of power in the electricity market. The main parts of a Wind Turbine System (WTS) are rotor, gearbox, generator, transformer and possible power electronic system (PES). Wind turbines require certain control systems. Horizontal-axis wind turbines have to be oriented to face the wind. In high winds, it is desirable to reduce the drive train loads and protect the generator and the power electronic equipment from overloading by limiting the turbine power to the rated value up to the furling speed. At gust speeds, the machine has to be stalled. At low and moderate wind speeds, the aim should be to capture power as efficiently as possible. The high efficient power electronics in power generation, power transmission/distribution and end-user application is being used to control.  This paper deals with the discussion and control of the most emerging renewable energy source, wind energy, with the help of PWM converter. Due to this power electronics system, it is changing from being a minor energy source to be acting as an important power source in the energy system